Insights into the Membranolytic Activity of Antimalarial Drug-Cell Penetrating Peptide Conjugates - Luísa Aguiar; Marina Pinheiro; Ana Rute Neves; Nuno Vale; Sira Defaus; David Andreu; Salette Reis; Paula Gomes (Membranes, 2020)
Conjugation of TP10, a cell-penetrating peptide with intrinsic antimalarial activity, to the well-known antimalarial drugs chloroquine and primaquine has been previously shown to enhance the peptide’s action against, respectively, blood- and liver-stage malaria parasites. Yet, this was achieved at the cost of a significant increase in haemolytic activity, as fluorescence microscopy and flow cytometry studies showed the conjugates to be more haemolytic for non-infected than for Plasmodium-infected red blood cells. To gain further insight into how these conjugates distinctively bind, and likely disrupt, membranes of both Plasmodium-infected and non-infected erythrocytes, we used dynamic light scattering and surface plasmon resonance to study the interactions of two representative conjugates and their parent compounds with lipid model membranes. Results obtained are herein reported and confirm that a strong membrane-disruptive character underlies the haemolytic properties of these conjugates, thus hampering their ability to exert selective antimalarial action.